1968
DOI: 10.2307/1934511
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Grazing by Tadpoles on the Structure of a Periphyton Community

Abstract: The species composition and standing crop of the algal epiphytes on the walls of experimental cages in a small lake were greatly altered following the emergence of frog tadpoles from eggs laid in the cages. The results support the hypothesis that tadpoles may be a major cause of the massive spring reduction in standing crop of filamentous green algae in the lake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 2 publications
9
80
0
Order By: Relevance
“…Because the food items were not identified to species, there is the possibility that the larvae could be feeding on entirely different species within broad categories. The evidence gathered on scraping and chewing larvae that are indiscriminate feeders (Dickman, 1968 andFarlowe, 1928), suggests that the larval species in this study are basically ingesting the same foods. Intuitively, it would seem that beakless larvae, by the nature of their feeding mechanism could discriminate particle size, but not composition.…”
Section: Hea(j-bo(dy Length Numbers In Parentheses Indicate Reduced mentioning
confidence: 64%
See 1 more Smart Citation
“…Because the food items were not identified to species, there is the possibility that the larvae could be feeding on entirely different species within broad categories. The evidence gathered on scraping and chewing larvae that are indiscriminate feeders (Dickman, 1968 andFarlowe, 1928), suggests that the larval species in this study are basically ingesting the same foods. Intuitively, it would seem that beakless larvae, by the nature of their feeding mechanism could discriminate particle size, but not composition.…”
Section: Hea(j-bo(dy Length Numbers In Parentheses Indicate Reduced mentioning
confidence: 64%
“…In fact, Farlowe (1928) found that examining the algal contents in tadpole guts was a superior method of determining the species composition of pond algae than were her collecting methods. Dickman (1968) found that larvae of Rana aurora strongly reduced the FIGURE 6. Comparative larval gut lengths.…”
Section: Gut Contentsmentioning
confidence: 98%
“…Although it is possible that L. catesbeianus tadpoles accumulate natural dietary sources of toxins, our methodology of maintaining tadpoles in the laboratory for a 1-mo period and feeding them a laboratory diet decreases the likelihood of tadpoles expressing toxins that were accumulated from natural dietary sources. Further, for tadpoles to accumulate toxins through their diet would require tadpoles to be selective foragers, which seems unlikely because tadpoles have been reported to be largely indiscriminate foragers (Dickman, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Dickman (1968) found that tadpole grazing reduced the diversity of periphyton and thus caused the community to approach a much lower level of maturity" Significant effects of terrestrial grazers on species composition were reported by Tomanek and Albertson (1953) and Hazell (1967)v but diversity indices were not calculated.…”
Section: Algae Present and Physical Appearancementioning
confidence: 98%
“…In the present study 5000 cm 2 were subjected to 5.2 g of small Phisa. Dickman (1968) ~w r : r n , · reported significant reduction in periphyton standing crop caused by tadpole grazing in a shallow pond.…”
Section: Algae Present and Physical Appearancementioning
confidence: 99%